2014
DOI: 10.1186/1472-6882-14-494
|View full text |Cite
|
Sign up to set email alerts
|

Pleurotus ostreatus opposes mitochondrial dysfunction and oxidative stress in acetaminophen-induced hepato-renal injury

Abstract: BackgroundAcetaminophen (APAP)-induced toxicity is a predominant cause of acute hepatic and renal failure. In both humans and rodents toxicity begins with a reactive metabolite that binds to proteins. This leads to mitochondrial dysfunction and nuclear DNA fragmentation resulting in necrotic cell death. Pleurotus ostreatus (an edible oyster mushroom) is well recognized as a flavourful food, as well as a medicinal supplement. In the present study, we evaluated the role of Pleurotus ostreatus in the protection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 53 publications
4
17
0
1
Order By: Relevance
“…[60][61][62] Several lines of studies suggested that free radical scavenging enzymes, i.e., SOD and GSH decreased and MDA, a lipid peroxidation end product increased when administered with APAP. 11 In line with previous studies 63,64 the present study also found significantly decreased SOD and GSH levels as well as increased MDA level during APAP treatment in the hepatic and renal tissue. Naringin treatment significantly enhanced tissue SOD and GSH as well as decreased MDA levels, demonstrating that naringin could maintain the abnormal antioxidant and ROS generation, which in turn modulate the membrane integrity against the APAPinduced cellular injury.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…[60][61][62] Several lines of studies suggested that free radical scavenging enzymes, i.e., SOD and GSH decreased and MDA, a lipid peroxidation end product increased when administered with APAP. 11 In line with previous studies 63,64 the present study also found significantly decreased SOD and GSH levels as well as increased MDA level during APAP treatment in the hepatic and renal tissue. Naringin treatment significantly enhanced tissue SOD and GSH as well as decreased MDA levels, demonstrating that naringin could maintain the abnormal antioxidant and ROS generation, which in turn modulate the membrane integrity against the APAPinduced cellular injury.…”
Section: Discussionsupporting
confidence: 93%
“…[89][90][91] Recently, in a mice model it has been shown that APAP-induced renal toxicity increases KIM-1 expression. 11 Similarly, in our study, we also observed significantly increased KIM-1 expression in APAPinduced renal toxicity. The exact mechanism behind the enhanced KIM-1 expression in APAP-induced renal toxicity is still not elucidated, but from our histopathological investigation, we can conclude that elevated KIM-1 expression in the renal tissue could be due to oxidative stress followed by necrotic cell death.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The overexpression of oxidative processes is involved in CRF patients and remains the significant factors for elevated morbidity and mortality in these patients [29]. Another research has showed that the balance between the production of reactive oxygen species (ROS) and the availability of antioxidant enzymes, such as SOD, BUN, MDA and GSH-Px, is consequently critical for avoiding the tissue damage induced by OS [30, 31]. GSH-Px, as one of the markers of oxidative stress, is highly expressed in RIF rats [32].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of acetaminophen-induced nephrotoxicity and hepatotoxicity has been reported by other investigators and showed that paracetamol causes oxidative stress and renal toxicity when used at high doses (21)(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 66%